Central levels of tryptophan metabolites in subjects with bipolar disorder - Trepci, Ada; Sellgren, Carl M.; Pålsson, Erik; Brundin, Lena; Khanlarkhani, Neda; Schwieler, Lilly; Landén, Mikael; Erhardt, Sophie (European neuropsychopharmacology, 2021)
The kynurenine pathway of tryptophan degradation produces several neuroactive metabolites such as kynurenic acid (KYNA), quinolinic acid (QUIN), and picolinic acid (PIC) thought to be involved in the pathophysiology of psychosis, major depression, and suicidal behavior. Here, we analyzed cerebrospinal fluid (CSF) concentrations of tryptophan, kynurenine, KYNA, QUIN, and PIC utilizing ultra-performance liquid chromatography – tandem mass spectrometry system (UPLC-MS/MS) in persons with bipolar disorder (n = 101) and healthy controls (n = 80) to investigate if the metabolites correlated with depressive symptoms or to the history of suicidal behavior. Furthermore, we analyzed if genetic variants of the enzyme amino-β-carboxymuconate-semialdehyde-decarboxylase (ACMSD) were associated with the CSF concentrations of PIC and QUIN. We found that CSF KYNA and PIC concentrations, as well as the kynurenine/tryptophan ratio were increased in bipolar disorder compared with controls. CSF PIC concentrations were lower in subjects with a history of suicidal behavior than those without, supporting the hypothesis that low CSF PIC is a marker of vulnerability for suicidality. Bipolar subjects taking antidepressants had higher CSF concentrations of kynurenine and KYNA than subjects not given these medications. A negative association was found between a genetic variant of ACMSD and the ratio of PIC/QUIN, indicating that a polymorphism in ACMSD is associated with excess of QUIN formation at the expense of PIC. The present results confirm that the kynurenine pathway is activated in bipolar disorder, and suggest that shifting the activity of the kynurenine pathway away from QUIN production towards a production of KYNA and PIC might be a beneficial therapeutic strategy.